Reduction of Bridge Pier Scour Through the Use of a Novel Collar Design - Valela, Christopher (Université d'Ottawa / University of Ottawa, 2021)
Bridge piers within moving water are exposed to an additional failure mechanism known as scour. Upon the scour depth reaching the foundation of the pier, the structural integrity of the pier, and consequently the bridge, can be jeopardized. Bridge pier scour is the result of a three-dimensional flow separation consisting primarily of the horseshoe vortex, flow acceleration along the sides of the pier, and wake vortices. There are numerous factors that can affect bridge pier scour, of which many of them have been studied extensively. However, there are still some factors where the knowledge base is limited: one example is the presence of an ice cover around bridge piers. In order to reduce the risk of failure induced by scour, regardless of the cause, a preferred option is to use scour countermeasures. However, an ideal countermeasure does not exist. Therefore, the purpose of this research is to design and test an improved bridge pier scour countermeasure, while also better understanding the effects an ice cover has on scour. Achieving a new countermeasure design consisted of a hybrid approach that combined both numerical and experimental modelling. The numerical model was used in an iterative manner to expedite the design process, as well as to reduce experimental costs. Upon testing and improving the initial collar design numerically, physical models were constructed for the purpose of testing experimentally. Experimental tests were performed at a 1:30 scale in the presence of a sand bed. The same experimental setup was used to investigate bridge pier scour under an ice cover, except a rigid structure was constructed to replicate an ice cover. The artificial ice cover possessed either a smooth or a rough underside and was installed in such a way to replicate a floating or fixed (pressurized) ice cover. The purpose of the new countermeasure design was to improve on the flat plate collar by guiding the horseshoe vortex in a novel manner. By doing so, the quantity of erosive forces contacting the bed was greatly reduced. In order to reach a final design, a series of prototype designs were tested, and are outlined in this thesis, as they provide valuable insight into the scour problem. The final countermeasure design resembles a contoured collar but is made of riprap, where it was found to reduce the scour depth and volume by 81.0% and 92.3%, respectively, while using 18% less riprap than the conventional flat riprap countermeasure. Upon investigating scour in the presence of an ice cover, it was found that the quantity of scour increases as the ice cover becomes rougher and as the flow becomes more pressurized beneath. Specifically, the scour depth under the rough ice cover and the most pressurized condition increased by 412%. It was demonstrated that implementing any device which increases the width of the pier has inherent limitations for reducing scour. Instead, having a depression around the pier, especially made of riprap, such that it is flush with the bed and can help guide the horseshoe vortex, was found to greatly reduce scouring. Furthermore, it was observed that the presence of any ice cover on the surface of the water generates greater pier scour, therefore necessitating that ice cover always be taken into consideration when designing bridges in cold climates.
Keywords: Bridge pier scour; Scour countermeasure; Ice cover